Loyalitas Customer Ditinjau dari Word of Mouth, Kualitas Produk dan Pelayanan Pada Da Astiti Dana di Mengwi Badung - Ni Putu Sri Mariyatni; Made Setena (Widya Manajemen, 2022)
This study aims to analyze customer loyalty in terms of word of mouth, product quality, and service, at DA Astiti Dana in Mengwi Badung. In this study, a quantitative approach was used. The population in this study were all 55 customers or regular customers of DA Astiti Dana in Mengwi Badung. The sampling technique uses a saturated sample or census technique, where the entire population is used as a sample. Analysis of the data used is multiple linear regression analysis, where previously the classical assumption was tested. The results of the analysis show a positive direction between word of mouth, product quality, and service to customer loyalty. Thus, it can be stated that the level of customer loyalty is influenced jointly by word of mouth, product quality, and service. The F-test test is a multiple linear regression coefficient significance test that shows that there is a simultaneous significant effect between the word of mouth, product quality, and service on customer loyalty. The significance test using the t-test shows that there is a partially significant effect between word of mouth, product quality, and service on customer loyalty.